Meta-Analysis Study: The Effects of Accountability and Transparency on Muzaki’s Trust in Zakat Institutions in Indonesia - Hotimah, Husnul; Suprayogi, Noven (Review of Islamic Economics and Finance, 2023)
Purpose – This study aims to analyze the relationship between transparency and accountability in influencing Muzaki’s trust in zakat institutions in Indonesia. Methodology - A quantitative approach with a meta-analysis method is used in this study to achieve that aim. This study uses ten previous research articles (papers) as research samples. The sample of this research was obtained from Google Scholar by going through a series of sample selection criteria. Findings - The findings of this study indicate that transparency and accountability affect Muzaki’s trust in zakat institutions in Indonesia in a significantly positive manner. Based on these findings, zakat institutions in Indonesia need to pay attention to the level of transparency and accountability and increase it to increase muzaki's trust in them